2000
DOI: 10.1046/j.1440-1819.2000.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐earthquake quality of life and psychological well‐being: Longitudinal evaluation in a rural community sample in northern China

Abstract: This study aims to observe longitudinal change of quality of life (QOL) and psychological wellbeing in a community sample affected by an earthquake and to examine the relationship between QOL and disaster exposure, post-disaster support and other related variables. The subjects, from two villages at different distances from the epicenter, were assessed using the brief version of the World Health Organization Quality of Life Assessment (WHOQOL-BREF) and three subscales of a symptoms checklist at 3 months (n = 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
103
1
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 12 publications
16
103
1
1
Order By: Relevance
“…Stress negatively affects either people with diabetes [24,29,35,36] or without [17][18][19][20][21][22]. Positive life events were associated with improved glycemic control; on the other hand, recent severe stressors were associated with poorer glycemic control [35].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stress negatively affects either people with diabetes [24,29,35,36] or without [17][18][19][20][21][22]. Positive life events were associated with improved glycemic control; on the other hand, recent severe stressors were associated with poorer glycemic control [35].…”
Section: Discussionmentioning
confidence: 99%
“…Supplies of insulin and other drugs for people with diabetes run out, and there is rapidly increased anxiety among diabetics [1,24]. Among the earthquake studies published between 1995 and 2000, few studies are involved with the impact of earthquakes on the quality of life (QOL) [26,29,30]. Wang et al [29] examined longitudinal change of QOL and psychological well-being in the aftermath of an earthquake.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous Chinese studies of lifestyles or QOL focused mainly on urban populations and patients or on specific populations, such as AIDS patients, HIV-infected heroin users, Bell's palsy patients, workers exposed to coal dust, rural-to-urban migrants, civil servants, professional drivers, and earthquake victims [14][15][16][17][18][19][20][21]. However, very few studies have examined whether and, if so, how QOL is associated with lifestyles and health among retired workers.…”
Section: Introductionmentioning
confidence: 99%
“…Xiangdong [13] found that the earthquake adversely affected the victims' quality of life in physical, psychological and environmental domains at 3 months and psychological and environmental domains at 9 months, after the disaster. When compared with the non-affected comparison group, the victims suffered significantly more psychological distress in terms of depression and anxiety.…”
Section: Well-beingmentioning
confidence: 99%